Zaryadye Placemaking - Ivanov, Andrei (project baikal, 2018)
The article touches on the challenge launched by the new Moscow Park against the orthodox ideas of city green spaces; the necessity of stakeholders’ conscious synergetic efforts to create sophisticated urban objects; and the possibility of an outstanding innovative placemaking solution in the heart of historic Moscow. The author positively characterizes the appropriate healing of the ‘hole in the landscape’ which used to be in Zaryadye; the solution for a new pedestrian fragment of the Moskva River embankment; and the creation of the environment with functional diversity suitable for today’s ’homo selfiens’. The author critically characterizes the correlation of the new structures of the park and the historic development of Varvarka Street; the lack of participation of the society in the development of the park; and the dominating administrative ‘top-down’ approach typical of Russia.